2020
DOI: 10.3233/wor-203221
|View full text |Cite
|
Sign up to set email alerts
|

Rising incidence of musculoskeletal discomfort in the wake of the COVID-19 crisis

Abstract: The COVID-19 pandemic has led to the shutdown of much of the world’s economic and social operations. Given shutdown of exercise facilities, there has been a sharp uptick in a sedentary lifestyle. As people have lost their normal daily activity patterns, it is reasonable to assume that musculoskeletal pain-related syndromes will consequently begin to increase. In addition, there has been a rise in social network, television, and online home-based workouts. In the wake of the COVID-19 pandemic, it is unclear whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
12
0
1
Order By: Relevance
“…There is insufficient studies investigating how lockdown affects musculoskeletal symptoms, although musculoskeletal symptoms are presumed to increase during the COVID-19 pandemic because people have lost their normal daily activity patterns through the lockdown and have become less physically active [18,19]. Fallon et al reported that the COVID-19 lockdown causes an increase in pain levels in people with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is insufficient studies investigating how lockdown affects musculoskeletal symptoms, although musculoskeletal symptoms are presumed to increase during the COVID-19 pandemic because people have lost their normal daily activity patterns through the lockdown and have become less physically active [18,19]. Fallon et al reported that the COVID-19 lockdown causes an increase in pain levels in people with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal symptoms are presumed to increase during the COVID-19 pandemic due to the fact that people have lost their normal daily activity patterns through the lockdown and have become less physically active [18,19]. Moretti et al have suggested that working from home during the COVID-19 pandemic causes worsening of musculoskeletal problems, particularly affecting the spine [20].…”
Section: Introductionmentioning
confidence: 99%
“…Such a strategy may also help to reduce heart attacks [29]. In addition, curfews and lockdowns implemented during COVID-19 pandemic have led to decreased physical activity, and because of such sedentary behavior the incidence of musculoskeletal pain is expected to rise [30,31]. However, individuals can adopt simple self-therapeutic approaches with home-based exercises to alleviate pain and postural problems during the pandemic [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…6 Özellikle pandemi döneminde sosyal izolasyonda evde kalan bireyler üzerinde yapılan çalışmalar; bireylerde fiziksel aktivite düzeylerinin azaldığı, kas iskelet sistemi ağrılarında ciddi bir artışın gözlemlendiği ve yaşam kalitesinin azaldığı yönünde tespitler sunmaktadır. [7][8][9][10] Bu durumun bireyler üzerinde başta kardiyovasküler hastalıklar, obezite ve diyabet olmak üzere birçok sağlık problemini tetiklediği ifade edilmektedir. 11…”
Section: Introductionunclassified